2019
DOI: 10.2134/age2018.11.0057
|View full text |Cite
|
Sign up to set email alerts
|

Genotype × Environment Interactions of Industrial Hemp Cultivars Highlight Diverse Responses to Environmental Factors

Abstract: Core Ideas Some hemp traits are more strongly affected by environmental factors than others. Multi‐environment testing is an integral part of hemp cultivar development. Water availability can have a significant impact on yield and other traits. Starting with the 2014 Farm Bill, hemp (Cannabis sativa L.) is being re‐introduced as an industrial crop in the United States. Since the crop has been absent for over 70 yr, little is known regarding the genetic mechanisms controlling economically relevant traits. Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 27 publications
(27 reference statements)
6
65
1
Order By: Relevance
“…There are only two published cannabis GWAS studies, one of which is ongoing and the other reporting marker‐trait association using a limited number of SNPs (B. J. Campbell et al ., 2019; Henry et al ., 2020; http://multihemp.eu/). The paucity of studies is likely a consequence of the previous limited accessibility of cannabis genetic diversity and insufficient marker density.…”
Section: Genomics Approaches That Could Be Applied In the Near‐term Tmentioning
confidence: 99%
“…There are only two published cannabis GWAS studies, one of which is ongoing and the other reporting marker‐trait association using a limited number of SNPs (B. J. Campbell et al ., 2019; Henry et al ., 2020; http://multihemp.eu/). The paucity of studies is likely a consequence of the previous limited accessibility of cannabis genetic diversity and insufficient marker density.…”
Section: Genomics Approaches That Could Be Applied In the Near‐term Tmentioning
confidence: 99%
“…However, the CBDA, differs in respect to DW yield between growth stages. Campbell et al [39] reported, that 83% of variance in CBD/A content resulted from genetic effects, making genotype selection important when seeking high CBD/A contents. Environmental factors such as the positive correlation between CBD/A content and water availability found by Calzolari et al [23] slightly increase CBD/A content, but the change was small enough that inflorescence yield is far more important to overall yield than a slight change in CBD/A percentage [39].…”
Section: Genotypementioning
confidence: 99%
“…Hemp ( Cannabis sativa L.) is a multiuse crop grown primarily for grain, fiber, and cannabinoids. In recent years, there has been a resurgence in the study of hemp in the United States and across the world in fields including genomics (Grassa et al, ; Laverty et al, ), agronomics (Campbell, Berrada, Hudalla, Amaducci, & McKay, ), and novel end‐uses (Turner, Sloan, & Currell, ; Wang & Xiong, ). The market for hemp (defined as <0.3% tetrahydrocannabinol; THC by dry weight) and marijuana (>0.3% THC), is expected to surpass $26 billion in the US by 2025 (Global Cannabis Report: 2019 Industry Outlook, ).…”
Section: Introductionmentioning
confidence: 99%